School of Scandinavian, Finnish, Dutch and Greek languages - O. E. Krasova (Vestnik MGIMO-Universiteta)
The school of Scandinavian, Finnish, Dutch and Greek languages has a long tradition teaching and research. The textbooks produced at the department are popular and widely used throughout the country. The department's faculty also conducts research, reflected in numerous publications.